Lithium‐Ion Batteries: Elucidating the Effect of Iron Doping on the Electrochemical Performance of Cobalt‐Free Lithium‐Rich Layered Cathode Materials (Adv. Energy Mater. 43/2019). Issue 43 (20th November 2019) - Wu, Fanglin; Kim, Guk‐Tae; Kuenzel, Matthias; Zhang, Huang; Asenbauer, Jakob; Geiger, Dorin; Kaiser, Ute; Passerini, Stefano
Abstract : In article number 1902445, Guk‐Tae Kim, Stefano Passerini, and co‐workers reveal the impact of iron doping on the performance fading mechanism of Co‐free Li‐rich (LRNM) layered oxide positive electrode materials. The introduction of iron reduces nickel migration into the transition metal layer and helps to suppress the accompanying structural transformation, the root cause of the voltage fading of LRNM‐layered cathodes.